Evidence of the gastroprotective and anti-helicobacter pylori activities of β-mangostin isolated from Cratoxylum arborescens (Vahl) blume - Sidahmed, H.M.A.; Hashim, N.M.; Mohan, S.; Abdelwahab, S.I.; Taha, M.M.E.; Dehghan, F.; Yahayu, M.; Ee, G.C.L.; Loke, M.F.; Vadivelu, J. (Dove Medical Press, 2016)
Purpose: β-Mangostin (BM) from Cratoxylum arborescens demonstrated various pharmacological activities such as anticancer and anti-inflammatory. In this study, we aimed to investigate its antiulcer activity against ethanol ulcer model in rats. Materials and methods: BM was isolated from C. arborescens. Gastric acid output, ulcer index, gross evaluation, mucus production, histological evaluation using hematoxylin and eosin and periodic acid–Schiff staining and immunohistochemical localization for heat shock protein 70 (HSP70) and Bax proteins were investigated. Possible involvement of reduced glutathione, lipid peroxidation, prostaglandin E2, antioxidant enzymes, superoxide dismutase and catalase enzymes, radical scavenging, nonprotein sulfhydryl compounds, and anti-Helicobacter pylori were investigated. Results: BM showed antisecretory activity against the pylorus ligature model. The pretreatment with BM protect gastric mucosa from ethanol damaging effect as seen by the improved gross and histological appearance. BM significantly reduced the ulcer area formation, the submucosal edema, and the leukocytes infiltration compared to the ulcer control. The compound showed intense periodic acid–Schiff staining to the gastric mucus layer and marked amount of alcian blue binding to free gastric mucus. BM significantly increased the gastric homogenate content of prostaglandin E2 glutathione, superoxide dismutase, catalase, and nonprotein sulfhydryl compounds. The compound inhibited the lipid peroxidation revealed by the reduced gastric content of malondialdehyde. Moreover, BM upregulate HSP70 expression and downregulate Bax expression. Furthermore, the compound showed interesting anti-H. pylori activity. Conclusion: Thus, it could be concluded that BM possesses gastroprotective activity, which could be attributed to the antisecretory, mucus production, antioxidant, HSP70, antiapoptotic, and anti-H. pylori mechanisms.